CASE REPORT: INTRADUCTAL PAPILLOMA OF THE MALE BREAST - Oliveira Júnior, José Alano Costa; Milani, Vivian; Andreghetto, Herbert Franchi Teixeira; Santos, Anita Mayara Feitosa; Fontes, Emília Virginia Lima Curvelo (Mastology, 2019)
Breast benign tumors, intraductal papilloma and fibroadenomas are common conditions in women; however, they are very rare in males. In this study, we report the case of a male patient, 75 years old, presenting with complaint of bilateral gynecomastia and palpable retroareolar mass in the left breast. The patient was submitted to imaging tests and core biopsy, and the hypothesis of intraductal papilloma was confirmed upon anatomopathological study. The mastology team opted for excision of the lesion and correction of gynecomastia.